ISOLATION AND IDENTITY IN DICKINSON: A PSYCHOANALYTIC APPROACH - Manu, Yohana Engelina Manurak; Winardi, Yohanes Kurniawan (Universitas Negeri Surabaya, 2025)
This study examines Emily Dickinson’s poem The Soul Selects Her Society through a Freudian psychoanalytic lens, with particular focus on the portrayal of identity. Using Sigmund Freud’s structural model of the psyche, the id, ego, and superego, this research investigates how the soul’s selective withdrawal functions as a defense mechanism for preserving selfhood. The analysis interprets the poem not as a mere act of social retreat but as a conscious assertion of individuality, in which the ego regulates instinctual desires and resists external pressures. Findings reveal that the soul’s rejection of societal appeals reflects the ego’s effort to maintain psychological boundaries, safeguard authenticity, and establish identity. Connections to Dickinson’s reclusive lifestyle and poetic style further demonstrate how her personal life resonates with this act of inward loyalty. Ultimately, the poem emerges as a literary articulation of the psyche’s negotiation of selfhood, showing identity as an active construction achieved through autonomy, resistance, and self-protection.